Does Community-Centred Performance Evaluation Exist? - Budavári, Árpád (Magyar Rendészet, 2022)
In this study the author wishes to examine the dominating aspects of performance evaluation of the general jurisdiction police in the relationship of the Hungarian police and society. His objectives are to introduce the system- and organisation-wide anomalies as well as to outline the drafts of a performance evaluation system that meets the needs of a community protected by the police. By using Hungarian and international literature on the topic he presents the integration of the Hungarian performance evaluation system into that of the public service and identifies the system- and organisation-wide anomalies. Through examples from his practice he presents the distortions these problems cause during performance evaluation. Eventually he proposes the introduction of program-based performance evaluation in Hungary.